2019
DOI: 10.3390/antiox9010024
|View full text |Cite
|
Sign up to set email alerts
|

Nanoantioxidants: Recent Trends in Antioxidant Delivery Applications

Abstract: Antioxidants interact with free radicals, terminating the adverse chain reactions and converting them to harmless products. Antioxidants thus minimize the oxidative stress and play a crucial role in the treatment of free radicals-induced diseases. However, the effectiveness of natural and/or synthetic antioxidants is limited due to their poor absorption, difficulties to cross the cell membranes, and degradation during delivery, hence contributing to their limited bioavailability. To address these issues, antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(116 citation statements)
references
References 135 publications
2
97
0
1
Order By: Relevance
“…The same effect was observed in the case of introduction the natural phenolic antioxidants like powdered rosemary ethanolic extract into the PLA matrix [39]. The literature shows the evaluation of antioxidant efficacy of synthesized AgNPs using 1,1-diphenyl-2-picryl hydrazyl radical (DPPH) [40], H 2 O 2 [41], ABTS radical cation scavenging, and FRAP assays [42]. It was reported that the DPPH and ABTS cation radical scavenging activity of AgNPs increased with the increase in the concentration of AgNPs [40,42].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The same effect was observed in the case of introduction the natural phenolic antioxidants like powdered rosemary ethanolic extract into the PLA matrix [39]. The literature shows the evaluation of antioxidant efficacy of synthesized AgNPs using 1,1-diphenyl-2-picryl hydrazyl radical (DPPH) [40], H 2 O 2 [41], ABTS radical cation scavenging, and FRAP assays [42]. It was reported that the DPPH and ABTS cation radical scavenging activity of AgNPs increased with the increase in the concentration of AgNPs [40,42].…”
Section: Discussionsupporting
confidence: 57%
“…The literature shows the evaluation of antioxidant efficacy of synthesized AgNPs using 1,1-diphenyl-2-picryl hydrazyl radical (DPPH) [40], H 2 O 2 [41], ABTS radical cation scavenging, and FRAP assays [42]. It was reported that the DPPH and ABTS cation radical scavenging activity of AgNPs increased with the increase in the concentration of AgNPs [40,42]. The improved thermal stability of the antibacterial green nanocomposites containing PLA, poly(butylene adipate-co-terephthalate) (PBAT) and nanocrystal cellulose (NCC)-Ag nanohybrids was also demonstrated by thermal gravimetric analysis (TGA) [36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the release of more or less MH in the absorption site would not be a preponderant factor, since the process still depends on the physicochemical properties of the molecule in the biological milieu. However, it is important to consider that although the release mechanism of some large and small molecules from silica matrices has been widely reported [62], to our knowledge, there are no reports on the release mechanism of polyphenols from systems called nanoantioxidants [13,63] based on silica. Unveiling this mechanism could anticipate biological behavior and optimize the design of pharmaceutical formulations to improve oral bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome some of these drawbacks, bio-inspired, bio-mimetic, and smart materials, among others, have been developed [10][11][12]. An emerging strategy has been the development of systems called nanoantioxidants [13,14]. These systems are nanoparticles with intrinsic antioxidant activity and/or antioxidant-functionalized nanoparticles, in order to stabilize or improve the antioxidant activity, and produce materials with synergistic effects and more biocompatible, with applications as pharmaceutical excipients, food packaging or pharmaceutical carriers [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, nanoparticles have the competency to scavenge the free radicals, and they can play an important role in preventing various diseases linked with the free radicals attack on cells and biological targets 57,58 . In this context, various nanoparticles, such as silica nanoparticles, iron-oxide nanoparticles, cerium oxide nanoparticles, metal nanoparticles, and organic (i.e., melanin, lignin) nanoparticles have been designed and assessed for their potential free radical scavenging capacity (RSC) 18,30,[59][60][61][62] . Here, we have investigated the in vitro RSC of different Au and Ag nanoparticles employing ABTS assay.…”
Section: Resultsmentioning
confidence: 99%